A systematic review of in-hospital worsening heart failure as an endpoint in clinical investigations of therapy for acute heart failure. (1st January 2018) - Fonseca, Cândida; Maggioni, Aldo Pietro; Marques, Filipa; Araújo, Inês; Brás, Daniel; Langdon, Ronald B.; Lombardi, Carlo; Bettencourt, Paulo
Abstract: Background: In-hospital worsening heart failure (WHF) occurs frequently in patients hospitalized for acute heart failure (AHF) and has strongly negative prognostic associations. It may be a useful endpoint in studies of AHF management but important questions remain regarding optimization of its definition and variability in its incidence. Methods: Our objective was to survey the full extent of clinical interest in WHF and assess the impact of baseline variables and trial design on outcomes. PubMed, Embase, and BIOSIS were searched systematically for clinical studies that had in-hospital WHF as an endpoint. Differences in definitions of in-hospital WHF were reviewed for their potential impact on observed incidence of WHF and its associations with post-discharge outcomes. Results: The search identified 35 publications representing 13 interventional trials, 3 observational studies, several different classes of therapeutic agent, and 78, 752 patients overall. Incidence of in-hospital WHF varied greatly—from 4.2% to 37%. Concerning the impact of differences in the way in which WHF was defined, two important factors were physician determination of worsening and whether intensification of diuretic therapy alone was defined as a WHF event. Patients having in-hospital WHF were at substantially greater risk for death and longer length of stay during index hospitalizations, all-cause and heart-failure rehospitalization, cardiovascular complications, renal failure, all-cause death, cardiovascular death, and higher healthcare costs post-discharge. Conclusions: There is diverse interest in selecting in-hospital WHF as an endpoint in clinical trials. Differences in reported incidence are complexly related to differences in the way in which WHF is defined.